PELATIHAN PEMBUATAN MEDIA ALAT PERAGA DI SMP KETAPANG III CIBUBUR - Malau, Nya Daniaty (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2025)
This community service program was designed to enhance the competencies of teachers and students at SMP Ketapang III Cibubur in developing innovative instructional media and teaching aids. The initiative was motivated by the limited utilization of teaching aids in the school's teaching and learning activities, which has adversely affected students’ comprehension of subject matter. The implementation of the program adopted a participatory training approach, involving five teachers and twenty-three selected students. The program comprised three main stages: (1) theoretical briefing on instructional media and the fundamental principles of teaching aid development, (2) practical workshops on constructing teaching aids using simple and readily available materials, and (3) simulation sessions for the application of these media in classroom learning. The training focused on the development of six types of teaching aids: traffic lights, electric generators, water-powered cars, solar-powered cars, magnetic trains, and scribble bots. All stages were deliberately designed to foster and optimize collaboration between teachers and students. Both groups exhibited strong enthusiasm during the demonstration sessions, actively participating and taking turns in observing and operating the teaching aids. Furthermore, they engaged in meaningful discussions by inquiring about the processes involved in constructing the teaching aids and the scientific principles underlying their operation. Based on the results of the satisfaction analysis, it was found that, out of fifteen assessment indicators, the overall satisfaction level was categorized as “very good,” indicating that the partner institution was highly satisfied with the activities conducted by the community service team. This program not only contributed to the improvement of teachers’ pedagogical competencies but also stimulated students’ creativity. In the long term, it is expected to promote the establishment of a collaborative learning culture between teachers and students through the effective use of instructional media.